Synthesis and Applications of Fluorocyclopropanes - Pons, Amandine; Poisson, Thomas; Pannecoucke, Xavier; Charette, André B.; Jubault, Philippe (Synthesis, 2016)
The combination of a fluorine atom and a cyclopropane ring, which both possess unique structural and chemical features, can generate new relevant scaffolds with potential interest for the synthesis of new bioactive compounds. In this review, we report the impressive progress recently devoted to the synthesis of fluorocyclopropanes especially using asymmetric methods and highlight some recent reported applications.1 Introduction2 Addition of Carbenes to Fluoroalkenes3 Addition of Fluorocarbenes to Alkenes4 Michael Initiated Ring Closure5 Nucleophilic Fluorination6 Applications to the Synthesis of Biorelevant Compounds7 Conclusion
Keywords: asymmetric synthesis; carbenes; cyclopropane; fluorine; fluoroalkenes; Michael reaction